Ecological Characteristics of Natural Habits of Deutzia paniculata, a Rare and Endemic Woody Species in Korea - Jin-Sun Park; 안종빈; 윤호근; 이명훈; 박완근; 신현탁; 홍용식; 이경철; 심윤진; Jung-Won Sung (Journal of forest and environmental science , 37(3), 2021)
Deutzia paniculata Nakai, a rare and endemic plant, has limited distribution throughout the North and South Gyeongsang provinces of South Korea. The D. paniculata community grows mostly on the stony slopes of forests, valley edges, and rock layers at 250-960 m in altitude, where deciduous trees are dominant and high humidity is maintained. Correlation analysis of vegetation and environmental factors found that the Walter’s dogwood-mulberry community was correlated with soil acidity (pH). Whilst the queritron community had correlations with distance from the valley, rock rate and slope. The natural habitat of the Palgongsan Mountain in Daegu is known to have high genetic diversity, had eight D. paniculata individuals recorded from 2014 to 2018, and 12 individuals recorded in 2020 (new individuals due to a newly created space within the herbaceous layer caused by grass mowing works), it is therefore unlikely that the community would perish unless there was an artificial disturbance. To conserve the natural habitats of D. paniculata, oppression by Sasa borealis, damage, increase in crown density of the upper layer, overexploitation, and absence of seedlings should be carefully investigated. In addition, response measures should also be established and the impact on seed fullness and the reproductive characteristics of D. paniculata recorded. To restore declined genetic diversity, individuals from high genetic diversity regions, such as Palgongsan Mountain, should be artificially transplanted. KCI Citation Count: 0